Menilai Keberhasilan Balanced Scorecard sebagai Sistem Pengukuran Kinerja Strategik - Tri Ramaraya Koroy (Universitas Muhammadiyah Yogyakarta, Indonesia, 2004)
This paper reviews the literature of Balanced Scorecard (BSC) as a strategic performance measurement tool. The research concerning the effectiveness of BSC indicate that BSC is a useful tool for communicating strategy, strategic learning and developing organizational culture. However, related research also shows that the implementation of BSC is not associated with economic benefit particularly for short-term period. This suggests that the adoption of BSC need a careful inquiry by the organization and the organization should not accept it as a ‘generic’ solution as a performance measurement tool.